If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -6 + 6x = -9x + -4x Reorder the terms: -6 + -1x + 6x = -9x + -4x Combine like terms: -1x + 6x = 5x -6 + 5x = -9x + -4x Combine like terms: -9x + -4x = -13x -6 + 5x = -13x Solving -6 + 5x = -13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13x' to each side of the equation. -6 + 5x + 13x = -13x + 13x Combine like terms: 5x + 13x = 18x -6 + 18x = -13x + 13x Combine like terms: -13x + 13x = 0 -6 + 18x = 0 Add '6' to each side of the equation. -6 + 6 + 18x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 18x = 0 + 6 18x = 0 + 6 Combine like terms: 0 + 6 = 6 18x = 6 Divide each side by '18'. x = 0.3333333333 Simplifying x = 0.3333333333
| 2y-12x=5 | | 70=2.5t+25 | | 1y-10=-2 | | 4d-4d^2=1 | | -z-z=3z+7+6z | | 84=3w^2 | | 10r-r^2=9 | | 4y-9=-57 | | 3y^2+15=87 | | 0.6x-1.2=2.5x+2.7 | | 0.6x-1.2=2.5x+2.7 | | D=2.5(7)+25 | | 15n(n+3)=0 | | 0.6x-1.2=2.5x+2.7 | | 15n(n+3)=0 | | 0.6x-1.2=2.5x+2.7 | | 15n(n+3)=0 | | D=2.5(7)+25 | | 7a+a-a+3ab-an+2ab= | | (9T^3n^5)(-2tn^2)=tn | | d-24=10 | | d-24=10 | | d-24=10 | | 7[2-(2+4x)]-2x=-9+2(1-15x) | | 4x+10=68 | | X-0.10x=15.72 | | 6(4x+4)=-24 | | 0=2v^2-64 | | x^2-5x=23 | | 2(3n+2)=7(5n+8)+8 | | 30=2.5t+25 | | 3.18=3.2 |